Laboratory manual in biochemistry - Cruz, Maribel Beltran; Montales, Signor Rinno Danao (Mandaluyong City Books Atbp. Pub., 2004)
Aims to provide general biochemistry experiments to students which could help them understand the concepts and skills that are related to the said subject. Intended for the use of General Biochemistry students and teachers.
Keywords: Biochemistry -- Laboratory manuals; Biochemistry -- Experiments